Genome-Wide Characterization of the C-repeat Binding Factor (CBF) Gene Family Involved in the Response to Abiotic Stresses in Tea Plant (Camellia sinensis) - Hu, Zhe; Ban, Qiuyan; Hao, Jing; Zhu, Xiangxiang; Cheng, Yaohua; Mao, Junlin; Lin, Mengling; Xia, Enhua; Li, Yeyun (Frontiers in Plant Science, 2020)
C-repeat (CRT)/dehydration responsive element (DRE)-binding factor CBFs, a small family of genes encoding transcriptional activators, play important roles in plant cold tolerance. In this study, a comprehensive genome-wide analysis was carried out to identify and characterize the functional dynamics of CsCBFs in tea plant (Camellia sinensis). A total of 6 CBF genes were obtained from the tea plant genome and named CBF1-6. All of the CsCBFs had an AP2/ERF DNA-binding domain and nuclear localization signal (NLS) sequence. CsCBF-eGFP fusion and DAPI staining analysis confirmed the nuclear localization of the CsCBFs. Transactivation assays showed that the CsCBFs, except CsCBF1, had transcriptional activity. CsCBF expression was differentially induced by cold, heat, PEG, salinity, ABA, GA, MeJA and SA stresses. In particular, the CsCBF genes were significantly induced by cold treatments. To further characterize the functions of CsCBF genes, we overexpressed the CsCBF3 gene in Arabidopsis thaliana plants. The resulting transgenic plants showed increased cold tolerance compared with the wild-type Arabidopsis plant. The enhanced cold tolerance of the transgenic plants was potentially achieved through an ABA-independent pathway. This study will help to increase our understanding of CsCBF genes and their contributions to stress tolerance in tea plants.